Family relationships and familial responses to health issues - Blair, Sampson Lee.; McCormick, Jennifer Higgins (Bingley, U.K. : Emerald, 2014)
Around the globe, families are often faced with a variety of health issues, often as a result of social, political, religious, and economic forces. Health issues affect not only individual family members, but also impact family relationships and structures. Illnesses, injuries, and health problems can strike at any time, and can have long-lasting consequences for families. When a family members health is in jeopardy, it can bring about a wide variety of dilemmas. This multidisciplinary volume addresses the impact these issues have on the family as a unit; how they impact family relationships as well as how the family as a whole responds. The chapters cover a wide range of health related topics including illness in adults and children, sexual relationships, mental health, and disability. Through the use of a wide variety of methodological and theoretical perspectives, the family scholars in this volume provide considerable insight into the ways in which families are affected by health, as well as how they adapt to and cope with health-related dilemmas.
In good and bad times? The influence of current relations with extended kin on negative life events / Martijn J.A. Hogerbrugge, Aafke E. Komter -- "No relationships, no emotions, just sex" : exploring undergraduates' sexual decision making in friends with benefits relationships / Christina L. Scott, Belinda Carrillo, Irma M. Rivera -- Multiple sclerosis and parenting : how our children respond to diagnosis, treatment, and daily life / Darbi J. Haynes-Lawrence, Adam R. West -- Extramarital relationships in the context of spousal Alzheimers' disease : a mixed-methods exploration of public attitudes / Andrew S. London, Janet M. Wilmoth -- Work-family conflict and depression for employed husbands and wives in Japan : moderating roles of self and spousal role involvement / Tetsushi Fujimoto, Sayaka K. Shinohara, Tsuyoshi Oohira -- Single mothers with breast cancer : relationships with their children / Amanda C. Ginter, Bonnie Braun -- Parental caregiving for a child with special needs, marital strain, and physical health : evidence from national survey of midlife in the U.S. 2005 / SunWoo Kang, Nadine F. Marks -- Mothers' perceptions of family communication patterns when having an ADHD child / Anita Hoag -- Families of children with autism spectrum disorder : the role of family-centered care in perceived family challenges / Jennifer S. Reinke, Catherine A. Solheim -- Multiple segment factorial vignettes in family health interventions / Marilyn J. Coleman, Lawrence H. Ganong, Jacquelyn J. Benson -- Black-white differences in formal ADHD diagnosis : unmet need, or conscious decision-making process? / Jessica Streeter.
Print version record
Keywords: Social Science -- Sociology / Marriage & Family; Family & Relationships -- General; Sociology: family & relationships; Family & health; Families -- Health and hygiene